Current Clinical Trials in Pemphigus and Pemphigoid - Izumi, Kentaro; Bieber, Katja; Ludwig, Ralf J. (Frontiers in Immunology, 2019)
Autoimmune bullous dermatoses (AIBDs) are a group of rare chronic inflammatory skin diseases, which clinically manifest as blisters and erosions of the skin and/or mucosa. Immunologically, AIBDs are characterized and caused by autoantibodies targeting adhesion molecules in the skin and mucosa. According to the histological location of the blistering, AIBDs are classified into the following two main subtypes: pemphigus (intraepidermal blistering) and pemphigoid (subepidermal blistering). Most AIBDs were potentially life-threatening diseases before the advent of immunosuppressive drugs, especially systemic steroid therapies, which suppress pathogenic immunological activity. Although there have been recent advancements in the understanding of the pathogenesis of AIBDs, glucocorticosteroids and/or adjuvant immunosuppressive drugs are still needed to control disease activity. However, the long-term use of systemic immunosuppression is associated with major adverse events, including death. Based on the growing understanding of AIBD pathogenesis, novel treatment targets have emerged, some of which are currently being evaluated in clinical trials. Within this article, we review the current clinical trials involving pemphigus and pemphigoid and discuss the rationale that lead to these trials. Overall, we aim to foster insights into translational research in AIBDs to improve patient care.